Incidencia de la equidad de género en la violencia por parte de los estudiantes del décimo año de educación general básica de la Unidad Educativa “19 de septiembre” – “Dr. Camilo Gallegos Dominguez”, en la provincia de Cotopaxi, ciudad de Salcedo en el periodo lectivo 2014 – 2015 - Sánchez Sánchez, Ximena del Rosario (2015)
This thesis was directed to "Develop workshops to promote gender equality and reduce violence by students in the tenth year of General Basic Education of the Education Unit September 19 - Dr. Camilo Gallegos Dominguez". Due to insufficient practice of values, unequal treatment that affect interpersonal relationships. To do this kind of research the following was used: field because it is performed in the scene with real information. Bibliographic documentary because it is based on research written sources. The school reflects the lack of equal treatment leads to committing violent acts in a way that limited their potential present and future. The Society was has responsible for developing stereotypes that affect students, assigning roles of behavior for men and women. In this regard it is proposed to develop workshops to strengthen the understanding of gender equity and equality; that contribute to optimize the relationship of the educational community, rescuing values and rejecting those patterns generated by society.